Search for the standard model Higgs boson produced in association with a W or a Z boson and decaying to bottom quarks - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Eroe, J; Fabjan, C; Friedl, M; Fruehwirth, R; Ghete, V; et al. (2014)
A search for the standard model Higgs boson (H) decaying to bb̄ when produced in association with a weak vector boson (V) is reported for the following channels: W(μν)H, W(eν)H, W(τν)H, Z(μμ)H, Z(ee)H, and Z(νν)H. The search is performed in data samples corresponding to integrated luminosities of up to 5.1 inverse femtobarns at √s=7 TeV and up to 18.9 fb-1 at √s=8 TeV, recorded by the CMS experiment at the LHC. An excess of events is observed above the expected background with a local significance of 2.1 standard deviations for a Higgs boson mass of 125 GeV, consistent with the expectation from the production of the standard model Higgs boson. The signal strength corresponding to this excess, relative to that of the standard model Higgs boson, is 1.0±0.5. © 2014 CERN. Published by the American Physical Society under the terms of the Creative Commons Attribution 3.0 License. Further distribution of this work must maintain attribution to the author(s) and the published article's title, journal citation, and DOI.